2008
DOI: 10.1203/pdr.0b013e318163a215
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Atrial Natriuretic Peptide and Its Receptor In the Lung: Effects on Perinatal Surfactant Release

Abstract: ABSTRACT:During the transition at birth to air breathing, regulation of surfactant release from alveolar type II (ATII) cells is critical. Atrial natriuretic peptide (ANP) stimulates natriuretic peptide receptor-A (NPR-A) and increases intracellular cGMP. We examined the changes in ANP and NPR-A in respiratory epithelium during the perinatal period using immunohistochemistry and studied the effect of ANP on surfactant release from ATII cells isolated from fetal and newborn lambs. NPR-A mRNA was detected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Natriuretic receptors have been identified in the epithelia of the bronchioles and Type I/II alveolar cells (20). ANP signals epithelial cells via basolateral natriuretic peptide receptor A, causing changes in G proteins, and an increase in intracellular cyclic guanosine 3',5'-monophosphate (56).…”
Section: Purinergic Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Natriuretic receptors have been identified in the epithelia of the bronchioles and Type I/II alveolar cells (20). ANP signals epithelial cells via basolateral natriuretic peptide receptor A, causing changes in G proteins, and an increase in intracellular cyclic guanosine 3',5'-monophosphate (56).…”
Section: Purinergic Activationmentioning
confidence: 99%
“…ANP signals epithelial cells via basolateral natriuretic peptide receptor A, causing changes in G proteins, and an increase in intracellular cyclic guanosine 3',5'-monophosphate (56). Activation of the natriuretic peptide receptor inhibits apical sodium absorption in the kidneys and intestines (68) and inhibits ENaC in Type II alveolar cells (20). Olivera et al (59) reported that when pulmonic circulation pressure was kept constant, the perfusion of ANP increased epithehal permeability and reduced Na^ absorption in isolated rat lung.…”
Section: Purinergic Activationmentioning
confidence: 99%
“…All protocols were approved by the Institutional Animal Care and Use Committee (IACUC) of the State University of New York at Buffalo. The technique utilized for the isolation and culture of ATIIs has been characterized in detail previously by our laboratory and is outlined briefly (5). For fetal lambs (136 days of gestation, full term is 145 days), pregnant ewes were anesthetized by an intravenous injection of pentobarbital sodium (2.3 mg/kg) and placed under isoflurane (1.5%) general anesthesia.…”
Section: Isolation Of Atiis From Fetal and Newborn Lambsmentioning
confidence: 99%
“…We previously reported that both ANP and its primary receptor, NPR-A, are highly expressed in ATIIs in the fetal lung before birth, but that shortly after birth this expression disappears (5). ANP at 10 − 10 M stimulated surfactant secretion in fetal and newborn sheep ATIIs.…”
mentioning
confidence: 92%
“…The literature data on the ANP-ontogeny refer to heart [13][14][15], brain [16][17][18], and lung [19]. The morphology of developing salivary glands was described in rat [20,21], mouse [22], miniature pig [23], and in humans [24].…”
Section: Introductionmentioning
confidence: 99%